An efficient deep learning approach to detect skin cancer using image data - Chowdhury, Yaser Al Rahman; Ahmed, S.K.Saqlayen; Faisal, Abdullah All; Zahir, Zerjiss (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.